The Effect of Internal Audit Effectiveness, Auditor Responsibility and Training in Fraud Detection - George Drogalas; Michail Pazarskis; Evgenia Anagnostopoulou; Angeliki Papachristou (Journal of Accounting and Management Information Systems (JAMIS), 2017)
The purpose of this study is to explore the relationship between internal audit effectiveness, internal auditor's responsibility, training and fraud detection. During the last decade internal auditing has become an integral part of modern businesses since it is capable of detecting errors or offences which lead to fraud. In order to investigate the above relationship, we conducted a survey of companies listed in the Athens Stock Exchange. We used factor analysis to validate the survey instrument and to construct our variables measuring fraud detection, internal audit effectiveness, auditor responsibility and training. We used regression analysis to test for significance between the constructed variables. Our analysis shows that audit effectiveness, auditor responsibility and auditor training affect positively and significantly the detection of fraud. Our results highlight the importance of internal audit in detecting accounting fraud and the need of companies to invest on internal audit processes and training in order to achieve enhanced corporate performance. Finally, our research stresses the importance of internal audit and fraud detection for companies which operate in countries which are in a period of economic crisis.
Keywords: M40; M41; M42; 650; Internal audit; auditor responsibility; auditor training; fraud detection; accounting fraud